Combination therapy with pulmonary arterial hypertension targeted drugs and immunosuppression can be a useful strategy for sarcoidosis-associated pulmonary hypertension: a case report. Issue 1 (16th December 2020) - Sumimoto, Keiko; Taniguchi, Yu; Emoto, Noriaki; Hirata, Ken-Ichi
Abstract: Background: Pulmonary hypertension (PH) is one of the significant complications of sarcoidosis. In the clinical classification of PH proposed in the recent world symposium of PH 2018, sarcoidosis-associated PH is classified in Group 5. The mechanisms of sarcoidosis-associated PH are very heterogeneous. There is no evidence of effective treatment for this condition. Case summary: We report a case of a 46-year-old female who developed severe pulmonary hypertension due to sarcoidosis. Her haemodynamics, exercise capacity, and functional class remarkably improved after the treatment with pulmonary arterial hypertension (PAH) targeted drugs including macitentan and tadalafil and secondary immunosuppressive therapy with corticosteroids. Discussion: This case emphasizes the importance of considering the underlying mechanisms of sarcoidosis-associated PH in order to choose appropriate treatment.